Development of a core collection from Sri Lankan traditional rice (Oryza sativa) varieties for phenotypic and genetic diversity - Shyama Weerakoon; Seneviratne Somaratne (Nusantara Bioscience, 2021)
Abstract. Weerakoon SR, Somaratne S. 2021. Development of a core collection from Sri Lankan traditional rice (Oryza sativa) varieties for phenotypic and genetic diversity. Nusantara Bioscience 13: 61-67. A collection of over 2000 traditional rice varieties are conserved at Gene Bank, Plant Genetics Resource Center, Sri Lanka. Oryza sativa varieties grown in Sri Lanka from ancient times to the middle of the last century are known as traditional rice. These varieties show adaptability to biotic and abiotic stresses and, an important component of biodiversity of Sri Lanka. A detailed understanding of the diversity of traditional rice varieties is essential for effective utilization of rice genetic resources and identification of potential parents possessing valuable genetic traits for future crop improvement. Study objectives were phenotypic and molecular characterization of one-hundred traditional rice varieties and to identify a core collection for phenotypic and genetic diversity. Rice varieties were grown in a plant house following RCBD with 4 replicates and 5 plants per replicate. Thirty-two agro-morphological characters were observed/collected. Genomic DNA was extracted from 20-days-old seedlings. Thirty?three microsatellite (Simple Sequence Repeat-SSR) primer pairs were used to assay genetic variation and PCR products were subjected to fragment analysis by capillary electrophoresis. Descriptive statistics and basic inferential statistical analyses were performed to access variation of agro-morphological characters among rice varieties. Cluster analysis and Multidimensional scaling produced 07 groups which were further analyzed using Classification and Regression Analysis to extract the diagnostic agro-morphological features. Groups of rice varieties were characterized by lemma palea color, awn color at maturity, seedling height, and flag-leaf angle. Traditional varieties represent distant clusters on agro-morphological features. Molecular analyses revealed all 33 loci displayed polymorphism (66.7-96.9%) among 100 traditional rice varieties with a total of 387 alleles identified with an average of 11.72 alleles per variety. All varieties were genetically structured into fifteen well-separated groups. UPGMA analysis based on Jaccard's similarity separated varieties into 05 major clusters. Genetic diversity information is useful in the efficient use of Sri Lankan rice germplasm and managing in situ and ex situ germplasm collections in conserving traditional rice varieties.